Exploring Social Capital and Agribusiness Systems of Transmigrants in the Early Settlement Phase: a Case Study in Wasile District - Basuki, Natal; Sangadji, Suwandi S.; Suhardi, Suhardi; Mahmud, Haris (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
This research was conducted in a transmigrant settlement in Wasile District, East Halmahera Regency, North Maluku Province, where the initial placement included ethnic groups from Banyuwangi and Banyumas. The study aims to analyze the support of social capital for the adaptability of transmigrants. A post-positivist paradigm was employed in this research. Data were collected through observation, participatory observation, in-depth interviews, focus group discussions, and document reviews. The informants consisted of 6 key informants and 14 supporting informants. The key informants included two representatives each from the Banyuwangi and Banyumas transmigrant groups placed in 1983, a Field Extension Officer (PPL), the Wasile District Head, the Village Head of Bumi Restu, and the Village Head of Mekar Sari. The supporting informants were those recommended by the key informants. The informants were selected purposively, followed by a snowball sampling technique. The data were analyzed qualitatively and descriptively manner. The findings indicate that the social capital support possessed by these two transmigrant groups significantly enhanced their adaptability, enabling them to survive and thrive. Furthermore, the implications of these findings are substantial. Strong social capital among the transmigrants can facilitate knowledge exchange, resource sharing, and collective action, essential for establishing and maintaining effective agribusiness practices. This robust support network enables transmigrants to overcome agricultural production, market access, and economic integration challenges. Consequently, the enhanced adaptability fostered by social capital improves their resilience and contributes to the overall success and sustainability of their agribusiness ventures, promoting community development and economic growth in the region.